A simple gas introduction system for cryogenic powder X‐ray diffraction. Issue 4 (29th July 2021) - Hodyss, Robert; Vu, Tuan H.; Choukroun, Mathieu; Cable, Morgan L.
Abstract : A simple system is described for the introduction and deposition of volatiles into standard X‐ray diffraction capillaries while they are mounted in situ in the X‐ray beam for X‐ray diffraction analyses. Abstract : A simple system is described for the introduction of gases into standard X‐ray diffraction capillaries mounted in situ in the X‐ray beam of laboratory X‐ray diffraction instruments. This system retains many of the advantages of the standard Norby cell, but does not require custom machining and has less stringent space restrictions. The system has been used to study the crystallization and interaction of volatile organics at cryogenic temperatures, but gas–solid interactions could also be studied at elevated temperatures using this approach.